Boundary objects supporting students’ meaning-making during work placement in Norwegian Vocational Education - Øgård, Monika [Verfasser]; Hillen, Stefanie Andrea [Verfasser] (My University, 2025)
“This study investigates the use of boundary objects in vocational education and training (VET) as an approach to address the challenge of meaning making of VET concepts, often experienced by pupils at school just as ‘definitions’ to be learnt by heart or to be memorized, hence becoming isolated knowledge instead of contextual applicable and meaningful. A problem that is well known in international dual VET education and research. As well it turns the focus on, for instance pupils, to potentially become co-brokers between the boundary of school and workplace, using boundary objects, reified as thematic assignments in and for both learning sites. In the interplay between boundary objects, advisors, students and teachers, affordances can be created helping to construct meaning and motivation in and for the pupils’ VET education.” (author’s abstract; BIBB-Doku)
Keywords: P 1.1 Jugendliche; L 3 Lehr-Lern-Forschung; L 1.1.2 Handlungs- und Lernfeldorientierung; 370; 300; Jugendlicher; Praktikum; Lehr-Lern-Forschung; Lern- und Arbeitsaufgabe; Sinngebung; Wahrnehmung; Norwegen